The life and work of Robert Burns - Shofe, Alice M. (My University, 1897)
Introduction: Any one visiting the many wild and picturesque scenes of Scotland, would excite expressions of surprise and consternation, should he refuse to visit the birthplace of Scotland’s songster, Robert Burns. Many travelers have turned aside that they might look for a few moments on the place so sacred to the Scottish people, and have given us, by the aid of their pens, a glimpse of what they saw and felt. The house built of clay in which Robert Burns was born still stands on the bank of the River Doon not far from the town of Ayr. More than a hundred years have passed since that cold stormy January day which saw the birth of nature’s truest poet. Humble surroundings marked his birth and life’s career. Poverty confronted him all his days but he never forgot the more needy. He was the eldest of seven children and was obliged at an early age to do considerable heavy work. Both he and his brother Gilbert, did mens work before they had reached the years of manhood. At the time of Robert’s birth we are told his father had rented a piece of ground and attempted to grow a nursery but he was not successful and in 1766 the family moved to Mount Oliphant, only to renew the old struggle. But they seem never to have lost hope. William Burns was a strong man in the best sense of the word, and his wife was a good and intelligent woman.
Citation: Shofe, Alice M. The life and work of Robert Burns. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: English; Robert Burns; Theses; Manuscripts (documents)